2023
DOI: 10.3389/ijph.2023.1605630
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults’ Perspectives on the Implications of an Augmented Reality Mobile Game for Communities’ Public Health: A Qualitative Study

Abstract: Objectives: Several physical, psychological, and social health consequences are caused by smartphone users’ addiction to games. A location-based game (LBG), Pokémon GO, recently garnered significant attention from young people. This study aims to explore their experiences with this game and motivations for playing, investigating their perspectives on the game’s implications for themselves and the public health of their communities.Methods: Ten qualitative focus group interviews were conducted. Young adults, ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Yip et al [ 11 ] and Xian et al [ 20 ] both explore the effects of playing Pokémon GO. Yip et al observed increased physical activity and social interactions among young adults in Hong Kong, though they noted risks like game addiction and accidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yip et al [ 11 ] and Xian et al [ 20 ] both explore the effects of playing Pokémon GO. Yip et al observed increased physical activity and social interactions among young adults in Hong Kong, though they noted risks like game addiction and accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement limitations and the need for further development of AR technologies highlight the preliminary nature of these interventions. These issues underscore the necessity for future research with larger, more diverse samples, rigorous control mechanisms, and comprehensive health assessments to strengthen the evidence base for AR interventions in public health [ 11 , 12 , 13 , 17 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%